Novel energy utilization mechanisms of microorganisms in the hydrosphere - Anhuai Lu; Jia Liu; Meiying Xu; Shungui Zhou; Juan Liu; Fanghua Liu; Yong Nie; Hongrui Ding; Yan Li (Fundamental Research)
This review focuses on new approaches adopted by microorganisms to acquire energy in oligotrophic and low-energy hydrosphere habitats, which involves increasing income, reducing expenditure and cooperation among different microorganisms. The various energy sources, electron transfer pathways and carbon, nitrogen, and sulfur cycles are involved in these processes. Specifically, this review delves into the potential molecular mechanisms on microbes utilizing photoelectrons from semiconducting minerals in natural photocatalytic systems. Also, it aims to reveal the regulation mechanisms of photoelectrons on interspecific electron transfer pathways and the energy synthesis processes in Geobacter, Pseudomonas, Halomonas and sulfate reducing bacteria, as well as the molecular mechanisms of perception and adaptation to different potentials of extracellular receptors and changes of oxygen gradients. Moreover, it demonstrates the network structure, formation and mechanisms of long-distance electron transfer driven by cable bacteria, particularly in the context of reducing CH4 and N2O coupled with the increase of dimethyl sulfide. This paper attempts to put forward new ideas for the energy utilization by microorganisms and their impact on element cycle in the hydrosphere, which contributes to a better understanding of the energy metabolism in interspecific, interspecies, and ecosystem contexts during the cycle-coupled processes of elements.